TNF Signaling in peritoneal mesothelial cells: pivotal role of cFLIPL - Lüdemann, Willie Magnus; Heide, Danijela; Kihm, Lars Philipp; Zeier, Martin; Scheurich, Peter; Schwenger, Vedat; Ranzinger, Julia (Peritoneal dialysis international, 2017)
Background: Peritoneal dialysis (PD) coincides with high concentrations of proinflammatory cytokines, such as tumor necrosis factor (TNF), in the peritoneal cavity. During treatment, chronic inflammatory processes lead to damage of the peritoneal membrane and a subsequent ultrafiltration failure. Human peritoneal mesothelial cells (HPMCs) play a central role as mediators and targets of PD-related inflammatory changes. Although TNF Receptor 1 (TNFR1) is expressed in high numbers on the cells, TNF-induced apoptosis is inhibited. Here, the underlying molecular mechanisms of TNFR1 signaling in HPMCs are investigated. Methods: Human peritoneal mesothelial cells were isolated from the omentum of healthy donors and the dialysis solution of PD patients. Flow cytometry was applied to determine cell surface expression of TNFR1 on HPMCS from healthy donors in absence or presence of TNF or PD fluid (PDF) and were compared to TNFR1 expression on cells from PD patients. To investigate TNFR1-mediated signaling, HPMCs were treated with PDF or TNF, and expression patterns of proteins involved in the TNFR1 signaling pathway were assessed by western blot. Results: Incubation with PDF led to a significant up-regulation of TNFR1 on the cell surface correlating with elevated TNFR1 numbers on HPMCs from PD patients. Investigations of underlying molecular mechanisms of TNFR1 signaling showed that PDF affects TNFR1 signaling at the proapoptotic signaling pathway by upregulation of IκBα and downregulation of cFLIPL. In contrast, TNF exclusively induces the activation of NFκB by an increase of phosphorylated IκBα. Conclusions: Novel and relevant insights into the mechanisms of TNFR1-mediated signaling in HPMCs with an impact on our understanding of PD-associated damage of the peritoneal membrane are shown.